Looking for a partner! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The National Farmers Association of Congo (ANAECO) of the Democratic Republic of Congo is looking for an external counterpart in the context of international cooperation, whose field of work focuses on agriculture, animal husbandry and sanitation....